(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The paper presents a general description of the functional and semantic types of speech contained in the textbook of the Russian language for experimental eleventh grade classes of the 12-year education model [1]. It analyzes the structure and methods of producing various types of speech – description, narration and argument determined in accordance with the purpose and content of speech. It also considers grammatical means used predominantly in a particular type of speech and emphasizes the possibility of the use of different types of speech within a text. The connection of various types of speech with functional styles is substantiated.